COLURIA GEOIDES (ROSACEAE) BAC INFLUENCE ON CELLULAR IMMUNE RESPONSE - S. V. Dutova; Yu. V. Rostovtseva; M. R. Karpova; M. A. Myadelets (Фармация и фармакология (Пятигорск), 2015)
The article presents the results of influence estimation of dry extract fractions of C. geoides (Rosaceae) at different stages of cell-mediated immune response in DHS reaction. Fraction of water-soluble BAC more actively stimulated the synthesis of pro-inflammatory cytokines at the stage of DHS solution